2022
DOI: 10.1007/s12144-022-02815-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of depression and anxiety among general population in Pakistan during COVID-19 lockdown: An online-survey

Abstract: The present study's aim is to find the prevalence of two of the common indicators of mental health - depression and anxiety – and any correlation with socio-demographic indicators in the Pakistani population during the lockdown from 5 May to 25 July 2020. A cross-sectional survey was conducted using an online questionnaire sent to volunteer participants. A total of 1047 participants over 18 were recruited through convenience sampling. The survey targeted depression and anxiety levels, which were measured using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 26 publications
4
16
0
Order By: Relevance
“…Implementing measures like lockdowns, while necessary for control, can induce anxiety responses and contribute to increased fear and prejudice against those infected or affected. 12 Studies examining the impact of COVID-19 on mental well-being not only shed light on critical areas of concern but also offer insights into how healthcare services can be equipped with essential information and support to provide mental health treatment to those in need. 13 Consequently, prioritizing public mental health is paramount, necessitating the adaptation of policies to support individuals in navigating the challenges posed by the "new normal."…”
Section: Inroductionmentioning
confidence: 99%
“…Implementing measures like lockdowns, while necessary for control, can induce anxiety responses and contribute to increased fear and prejudice against those infected or affected. 12 Studies examining the impact of COVID-19 on mental well-being not only shed light on critical areas of concern but also offer insights into how healthcare services can be equipped with essential information and support to provide mental health treatment to those in need. 13 Consequently, prioritizing public mental health is paramount, necessitating the adaptation of policies to support individuals in navigating the challenges posed by the "new normal."…”
Section: Inroductionmentioning
confidence: 99%
“…In addition to the direct impact of the virus, the pandemic has also led to economic instability, social isolation, and increased domestic violence, which have further exacerbated mental health issues [ 15 ]. According to a Pakistani study, there was a considerable rise in the prevalence of depression and anxiety symptoms throughout the pandemic, with healthcare workers experiencing the greatest rates [ 16 ]. In accordance with a different study, the epidemic has increased Pakistan's suicide rates, underscoring the urgent need for mental health interventions [ 17 ].…”
Section: Reviewmentioning
confidence: 99%
“…Studies elucidate how plants integrate external salt signals and internal developmental cues to regulate growth, development, and tolerance to salt stress. This regulatory mechanism involves multiple transcription factor families, including MYB, WRKY, and NAM/ATAF/CUC (NAC) [7][8][9], along with phytohormone, such as abscisic acid (ABA), auxin (AUX), brassinosteroid (BR), and gibberellin (GA) [10][11][12][13]. Notably, different transcription factors exhibit varying responses to salt stress.…”
Section: Introductionmentioning
confidence: 99%
“…These genes can offer insights into plants' strategies for adapting to salt stress [25][26][27]. With the rapid advancement of cotton genome research, several functional genes involved in the response to salt stress have been identified [8]. Studies have shown that overexpressing the transcription factors GhDof1 and GhABF2 in cotton enhances its tolerance to salt stress [28,29].…”
Section: Introductionmentioning
confidence: 99%